2017
DOI: 10.1177/2055217317730097
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of optic nerve atrophy in patients with multiple sclerosis

Abstract: BackgroundOptic neuritis (ON) is one of the most common presentations of multiple sclerosis (MS). Magnetic resonance imaging (MRI) of the optic nerves is challenging because of retrobulbar motion, orbital fat and susceptibility artifacts from maxillary sinuses; therefore, axonal loss is investigated with the surrogate measure of a single heuristically defined point along the nerve as opposed to volumetric investigation.ObjectiveThe objective of this paper is to derive optic nerve volumetrics along the entire n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…As history of previous ON was found to be associated with reduced OND and ONSD (Table 2) and patients with acute ON were found to have higher rates of previous ON (Table 1), it could be hypothesized that any potential thickening of the retrobulbar portion of the optic nerve in the setting of acute ON was counterbalanced by the previously induced optic nerve atrophy as a result of past ON episodes [15,16]. Indeed, in a further analysis comparing patients with first episode to the group of patients with recurrent episodes of ON, a significant difference regarding the OND was identified.…”
Section: Discussionmentioning
confidence: 99%
“…As history of previous ON was found to be associated with reduced OND and ONSD (Table 2) and patients with acute ON were found to have higher rates of previous ON (Table 1), it could be hypothesized that any potential thickening of the retrobulbar portion of the optic nerve in the setting of acute ON was counterbalanced by the previously induced optic nerve atrophy as a result of past ON episodes [15,16]. Indeed, in a further analysis comparing patients with first episode to the group of patients with recurrent episodes of ON, a significant difference regarding the OND was identified.…”
Section: Discussionmentioning
confidence: 99%
“…One important question that should be raised in interpretation of our results is whether the observed atrophy of the OC was owing to direct extension of the atrophic process (retrograde degeneration) from the adjacent ONs in association with optic neuritis, rather than a reflection on generalized brain atrophy associated with MS. We had hypothesized the latter, and indeed somewhat simplistically (in the context of this proof‐of‐principle study), avoided factoring in the presence or absence of ON optic neuritis precisely because it had been shown previously by Harrigan et al () that there was no difference in size of the ONs closest to insertion into the OC in MS patients, whether with or without prior optic neuritis—although both were thinner than in normal subjects. We acknowledge however that the issue may be much more complex as to whether the OC dimensions may be more affected by pathological involvement in the adjacent ON versus global WM atrophy that accompanies MS. For instance, Blanc et al () found atrophy of the OC in patients with neuromyelitis optica.…”
Section: Discussionmentioning
confidence: 92%
“…The OC is a WM structure that is often clearly visible on routine MRI and is anatomically related to the ONs, which are known to be affected in MS patients, whether with and without optic neuritis (Harrigan et al, ). In this study, we evaluated the morphometry of the OC in normal and MS patients to determine the feasibility of establishing a morphometric measure of atrophy that would be easier to derive than separate ON evaluation for atrophy, and that could potentially be obtained on routine clinical diagnostic MRI scans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations